Revitalisasi Pendidikan Agama Islam dalam Mewujudkan Profil Ulil Albab di Perguruan Tinggi - Syahdara Anisa Makruf (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
Universitas Islam Indonesia is the first and oldest university in Indonesia. Its existence as a university that represents Islamic values that carry out the mission of Rahmatan Lil Alamin to form students has a profile Ulil Albab through the process of coaching Islamic Religious Education carried out comprehensive This research method uses a qualitative naturalistic approach because the author is directly involved in the development activities of Islamic Religious Education at the Islamic University of Indonesia. The research subjects here are the Directorate of Islamic Religious Education (DPPAI) and lecturers of The Compulsory Uumum Lecture (MKWU) of Islamic Religious Education with research objects of PAI coaching activities. As for data analysts by reducing, presenting the data, and concluding. The results in this study found that the history of the establishment of the Ithe Islamic University of Indonesia is to bring together science and religion. Islamic Education development strategies include the establishment of Islamic personality through the planting of Islamic Basic Values (PNDI) and prophetic leadership through Basic Islamic Leadership Training (LKID) while learning strategies include transformative skills and integrative learning. This strategy needs to be revitalized because the Islamic University of Indonesia has the mind as a scientific center, Islamic center, an innovation center to spread the treatise of Islam Rahmatan Lil Alamin.